Pseudo-Archaic English: the Modern Perception and Interpretation of The Linguistic Past - Traxel, Oliver M. (Studia Anglica Posnaniensia, 2013)
This paper introduces a new project currently in its planning stages.1 It is dedicated to pseudoarchaic English, an area in linguistic studies which has so far hardly received any academic attention. After providing some historical examples a brief selection of some present-day occurrences as well as inspirational sources for these is given. Sample cases of pseudo-archaic English from various linguistic categories are presented in order to illustrate the wide range of its usage. Some remarks on modern perceptions of the linguistic past and their role in creating pseudo-archaic forms are provided and followed by suggestions on what still needs to be done in this field.